Fracture resistance of titanium, chrome-cobalt, and gold alloy as post and core materials: A comparative evaluation - Karunakaran Jeyaraman Venkataraman; Sathya Thanapathi; Sathyanarayanan Balasubramanian; Shrimanikandan Ayappa Gandhi; Anagha Chandrasekharan Sarojinikutty (Wolters Kluwer Medknow Publications, 2020)
Aim: This study aimed to comparatively evaluate the fracture resistance of different metallic post and core materials. Materials and Methods: Twenty-four maxillary-central incisors were selected, standardized, and segregated into three groups (GP I-III) (n = 8) based on the type of alloy used for post and core preparation. GP I (gold alloy [Au]), GP II (chrome-cobalt alloy [Co-Cr]), and GP III (titanium alloy [Ti]) were comparatively evaluated for use as post and core materials. The teeth were endodontically treated and tooth preparation for post core was done.Metal post and cores were fabricated using indirect wax pattern and luted. Teeth were mounted on resin bases, fracture testing was done, and type of fractures were analyzed. Results: Mesiodistal type of fracture was the most common among experimental groups with a percentage incidence of 54.20%. The comminuted type of fracture was the next most common with a percentage incidence of 29.2%. The incidence of buccolingual, transverse, and other type of fracture was not common and had a percentage incidence of 29.2%, 4.2%, 8.3% and 4.2% respectively. Group II had the highest fracture resistance with a mean value of 742.89N. Group III and Group I had mean values of 482.33 and 361.1123N. Statistically significant difference between experimental groups (I and II) and (II and III) was observed in load values of root fracture (P < 0.05). Conclusion: On the basis of the protocols used and limitations of this study, among metallic post and core materials tested, GP II had the highest fracture resistance values. Further evaluation of these different post and core systems, new alloy formulations designed specifically for use as post and core materials, and assessment in a clinical setting is recommended.